Corticospinal changes induced by fatiguing eccentric versus concentric exercise - Garnier, Y. M.; Paizis, C.; Lepers, R. (European Journal of Sport Science, 2019)
The present study assessed neuromuscular and corticospinal changes during and after a fatiguing submaximal exercise of the knee extensors in different modes of muscle contraction. Twelve subjects performed two knee extensors exercises in a concentric or eccentric mode, at the same torque and with a similar total impulse. Exercises consisted of 10 sets of 10 repetitions at an intensity of 80% of the maximal voluntary isometric contraction torque (MVIC). MVIC, maximal voluntary activation level (VAL) and responses of electrically evoked contractions of the knee extensors were assessed before and after exercise. Motor evoked potential amplitude (MEP) and cortical silent period (CSP) of the vastus medialis (VM) and rectus femoris (RF) muscles were assessed before, during and after exercise. Similar reductions of the MVIC (-13%), VAL (-12%) and a decrease in the peak twitch (-12%) were observed after both exercises. For both VM and RF muscles, MEP amplitude remained unchanged during either concentric or eccentric exercises. No change of the MEP amplitude input-output curves was observed post-exercise. For the RF muscle, CSP increased during the concentric exercise and remained lengthened after this exercise. For the VM muscle, CSP was reduced after the eccentric exercise only. For a similar amount of total impulse, concentric and eccentric knee extensor contractions led to similar exercise-induced neuromuscular response changes. For the two muscles investigated, no modulation of corticospinal excitability was observed during or after either concentric or eccentric exercises. However, intracortical inhibition showed significant modulations during and after exercise. Keywords: Single-joint exercise, concentric, eccentric, knee extensor muscles, neuromuscular fatigue